The Importance attributed to mandukya karika in the Tradition of advaida vedanta - Muhunthan, S. (South Eastern University of Sri Lanka, 2022)
Mandukya Karika possesses the classic quality of being the original treatise in the tradition of Advaita Vedanta. This was written by Goudapada who was the preceptor of Sri Adi Sankara. Being the very source of Vedanta tradition, it is exalted as the origin of Vedanta, as well as an Upadesa granta. Its author Goudapada has often been known as “sampradayavid” i.e the seed of Vedantic practices. Though known as a commentary on Mandukya Upanishad, basically its range of thought is of a profound nature. Thus, this work containing 215 Slokas in four chapters, accommodates within its self the unique properties of Advaita Vedanta.In its study of a causal relationship, Mandukyakarika clarifies the Sadkarana Vada of Advaita in its chapter on “Aladashanti”. It was mandukyakarika that first introduced Adi sankara’s Vivartavada to establish that this world is just an illusion and the illustration of the famous “Rope-snake” example. It was Mandukyakarika that paved the way for the advaitins to emphatically expound the subtle difference between the two states ‘Paramartika sat’ (the eternal truth) and ‘Vyapakarika sat (the temporal truth). Also, it was Mandukya Karika that introduced this famous concept known as ‘Ajativada’ to the Advaita school of thought. Mandukya Karika also proposed "asparisayoga" and "Pranava yoga" as the achievements required to gain advaitic experience.
Keywords: Mandukyakarika; Advaida Vedanta; Goudapada